Numerical and experimental investigations of the formation process of ferrofluid droplets - Liu, Jing (2012)
This paper reports both experimental and numerical investigations of the formation process of ferrofluid droplets in a flow focusing configuration with and without an applied magnetic field. In the experiment, the homogenous magnetic field was generated using an electromagnet. The magnetic field in the flow direction affects the formation process and changes the size of the droplets. The change in the droplet size depends on the magnetic field strength and the flow rates. A numerical model was used to investigate the force balance during the droplet breakup process. A linearly magnetizable fluid was assumed. Particle level set method was employed to capture the interface movement between the continuous fluid and the dispersed fluid. Results of the droplet formation process and the flow field are discussed for both cases with and without the magnetic field. Finally, experimental and numerical results are compared.